ANALISIS DAYA SAING EKSPOR PRODUK TIDAK DIOLAH PERTANIAN ASEAN KE NEGARA TUJUAN UTAMA - P. Christoman Siregar; Suardi Tarumun; Eliza Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to analyze the export position of unprocessed product by Indonesia agricultural in ASEAN countries and competitiveness exports of unprocessed product of agricultural in ASEAN countries for the main destination countries. In this research the data used is secondary data, that is the time series data during 10 years in period 2005-2014. The analysis method used is Constant Market Share (CMS). The export position of unprocessed product by Indonesia agricultural is highest value in ASEAN. The next position is Malaysia, Thailand, Vietnam, Singapore and Philippines. For the abilty of competitiveness, the highest position is Thailand. At the same time the next position is Vietnam, Philippines, Indonesia, Malaysia and Singapore. For the results of CMS analysis during period 2005-2014 based on four effects is shows the effect of influenced the competitiveness of agricultural unprocessed products are the effect of standard growth. Keywords: Agricultural unprocessed products, Competitiveness, Constant Market